Erythropoietin treatment in chronic renal failure anaemia-biosimilar option in the rational use of medicine process in order to reduced public health economic burden - Marin, Gustavo Horacio (2018)
Biopharmaceuticals innovation molecules have changed the course of a large number of chronic diseases. Many of these molecules became Gold Standards in oncology, rheumatology and other illness. However, their cost makes these drugs unattainable for most patients, and often put the health systems’ budgets at risk. This study takes the anaemia due to Chronic Renal Failure disease (CRFD) as an example to a rational selection of treatment with erythropoietin (EPO) and compares the trade brand mark of this drug with biosimilars option. Prescriptions of EPO in 394 patients with CRFD were submitted to a protocol of rational selection based in efficacy/risk ratio demonstration. This protocol was able to reduce that initial number to 91 cases that could really benefited with EPO treatment. These patients were included in a cohort study that compared EPO trade mark with biosimilars option. The experience demonstrated equal clinical outcomes in both groups but a reduction to half the original cost when biosimilars were dispensed. Biosimilars demonstrated to be a cheap and safe option to increase medicine access for anaemia associated to CRFD.